Evaluation of the efficacy of CAD/CAM glass-ceramic onlays in molars with complicated oblique crown fracture - FENG Ermei (口腔疾病防治, 2019)
Objective To evaluate the clinical efficacy of CAD/CAM glass-ceramic onlays in molars with complicated oblique crown fracture within 3.0 mm subgingival. Methods Fifty-six molars from 56 patients with complicated oblique crown fracture within 3.0 mm subgingival were recruited after endodontic treatment and divided into 2 groups according to the restorative methods used. The glass-ceramic onlays group was restored with CAD/CAM glass-ceramic onlays, while the all-ceramic crown group received CAD/CAM all-ceramic crowns. The success rates of the restorations were analyzed, and the sulcus bleeding index (SBI), plaque index (PLI), and gingival index (GI) were recorded at the prerestoration and postrestoration stages. Results After one year of follow-up, the success rate of the glass-ceramic onlay group was 96.4%, and the success rate of the all-ceramic crown group was 92.9%. The difference was not statistically significant (P > 0.05). No differences in SBI, PLI, or GI were found between the glass-ceramic onlay group and the all-ceramic crown group (P > 0.05). Conclusion Compared with all-ceramic crowns, CAD/CAM glass-ceramic onlays can be used as the choice of restoration for molar crowns with within 3.0 mm subgingival oblique fracture.